Question
upstudy study bank question image url

1367. а) \( 2 \cdot 4^{x}-5 \cdot 2^{x}+2=0 \) б) \( 3 \cdot 9^{x}-10 \cdot 3^{x}+3=0 \)

Ask by Warren Barker. in Uzbekistan
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

а) \( x = 1 \) и \( x = -1 \). б) \( x = 1 \) и \( x = -1 \).

Solution

а) Решим уравнение \( 2 \cdot 4^{x} - 5 \cdot 2^{x} + 2 = 0 \). **Шаг 1:** Сделаем замену переменной. Пусть \( y = 2^{x} \). Тогда \( 4^{x} = (2^{x})^{2} = y^{2} \). **Шаг 2:** Подставим замену в уравнение: \[ 2y^{2} - 5y + 2 = 0 \] **Шаг 3:** Решим полученное квадратное уравнение относительно \( y \). Вычислим дискриминант: \[ D = (-5)^{2} - 4 \cdot 2 \cdot 2 = 25 - 16 = 9 \] \[ y = \frac{5 \pm \sqrt{9}}{4} = \frac{5 \pm 3}{4} \] Получаем два корня: \[ y_1 = \frac{8}{4} = 2 \] \[ y_2 = \frac{2}{4} = \frac{1}{2} \] **Шаг 4:** Вернёмся к переменной \( x \). 1. \( 2^{x} = 2 \) ⇒ \( x = 1 \) 2. \( 2^{x} = \frac{1}{2} = 2^{-1} \) ⇒ \( x = -1 \) **Ответ:** \( x = 1 \) и \( x = -1 \). --- б) Решим уравнение \( 3 \cdot 9^{x} - 10 \cdot 3^{x} + 3 = 0 \). **Шаг 1:** Сделаем замену переменной. Пусть \( z = 3^{x} \). Тогда \( 9^{x} = (3^{x})^{2} = z^{2} \). **Шаг 2:** Подставим замену в уравнение: \[ 3z^{2} - 10z + 3 = 0 \] **Шаг 3:** Решим полученное квадратное уравнение относительно \( z \). Вычислим дискриминант: \[ D = (-10)^{2} - 4 \cdot 3 \cdot 3 = 100 - 36 = 64 \] \[ z = \frac{10 \pm \sqrt{64}}{6} = \frac{10 \pm 8}{6} \] Получаем два корня: \[ z_1 = \frac{18}{6} = 3 \] \[ z_2 = \frac{2}{6} = \frac{1}{3} \] **Шаг 4:** Вернёмся к переменной \( x \). 1. \( 3^{x} = 3 \) ⇒ \( x = 1 \) 2. \( 3^{x} = \frac{1}{3} = 3^{-1} \) ⇒ \( x = -1 \) **Ответ:** \( x = 1 \) и \( x = -1 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

Let's tackle these equations step by step! First, consider the equation \( 2 \cdot 4^{x}-5 \cdot 2^{x}+2=0 \). You can express \( 4^{x} \) as \( (2^2)^{x} = 2^{2x} \). Substituting this into the equation yields: \[ 2 \cdot 2^{2x} - 5 \cdot 2^{x} + 2 = 0. \] Now, let \( y = 2^{x} \). The equation transforms to: \[ 2y^2 - 5y + 2 = 0. \] You can apply the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) here. Next, for the equation \( 3 \cdot 9^{x}-10 \cdot 3^{x}+3=0 \), notice that \( 9^{x} \) can be expressed as \( (3^2)^{x} = 3^{2x} \). Replacing it gives: \[ 3 \cdot 3^{2x} - 10 \cdot 3^{x} + 3 = 0. \] Using the substitution \( y = 3^{x} \), the equation becomes: \[ 3y^2 - 10y + 3 = 0. \] Once again, the quadratic formula can help solve for \( y \). After solving for \( y \), you'll backtrack by substituting \( y \) back to find \( x \). Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy